2021
DOI: 10.3390/nu13082810
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterols, Cholesterol Control, and Cardiovascular Disease

Abstract: The use of phytosterols (or plant sterols) for the control of plasma cholesterol concentrations has recently gained traction because their efficacy is acknowledged by scientific authorities and leading guidelines. Phytosterols, marketed as supplements or functional foods, are formally classified as food in the European Union, are freely available for purchase, and are frequently used without any health professional advice; therefore, they are often self-prescribed, either inappropriately or in situations in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 64 publications
1
43
0
Order By: Relevance
“…Afterward, phytosterols are then esterified within enterocytes and incorporated in chylomicrons to reach the liver. Finally, hepatocytes secrete these phytosterols into the bile through ABCG5/G8 transporters [ 126 ]. Phytosterol composition, the characteristics of its food matrix, clinical conditions that affect cholesterol metabolism such as type 2 diabetes mellitus (DM2), and single-nucleotide polymorphisms (SNPs) in NPC1L1 and apolipoprotein E (ApoE) may modify both their bioavailability and their efficacy [ 126 , 127 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, phytosterols are then esterified within enterocytes and incorporated in chylomicrons to reach the liver. Finally, hepatocytes secrete these phytosterols into the bile through ABCG5/G8 transporters [ 126 ]. Phytosterol composition, the characteristics of its food matrix, clinical conditions that affect cholesterol metabolism such as type 2 diabetes mellitus (DM2), and single-nucleotide polymorphisms (SNPs) in NPC1L1 and apolipoprotein E (ApoE) may modify both their bioavailability and their efficacy [ 126 , 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…Beneficial effects of phytosterols on LDL-cholesterol are well established, with a mean reduction of 8–10% [ 294 ] and significant reductions in ApoCII and ApoE [ 295 ]. An extensive review of clinical trials with phytosterols in cardiovascular risk reduction was published elsewhere [ 126 ]. There is no definitive evidence on the impact of dividing the daily phytosterol intake on cholesterol metabolism [ 296 , 297 ]; therefore, further studies are needed to make recommendations.…”
Section: Resultsmentioning
confidence: 99%
“…After being transported to the liver, PSs can return to the intestine via ABC from the hepatobiliary interface [ 26 ]. There are those who have shown that the administration of PSs has led to a decrease in total cholesterol and LDL cholesterol by decreasing the absorption of cholesterol from the diet and the action on the intestinal and hepatic mechanisms [ 36 ].…”
Section: Phytosterols: Composition Occurrence and Biological Activitiesmentioning
confidence: 99%
“…Plant sterols and stanols (collectively known as phytosterols) have a polycyclic chemical structure similar to that of cholesterol with the exception of the side chain linked to the cyclopentane ring (19). They are almost absent in animal-based foods, but are found (in assorted amounts) in all plant-based products (20).…”
Section: Phytosterols Ie Plant Sterols and Stanolsmentioning
confidence: 99%